Strategi Komunikasi Pemasaran @Lapo Mandailing Coffee Pada Media Sosial Instagram di Kecamatan Panyabungan - Aisyah Melani; Effiati Yuliana Hasibuan; Agung Suharyanto (Universitas Medan Area, 2019)
The background of this reaserch is marketing communication used by Lapo Mandailing Coffee in Instagram as a popular social media nowdays. The purpose of this study is to determine the marketing communication strategy through social media Instagram and what factors are supporting and inhibiting in doing marketing communication strategy through social media instagram. Methode that use in this study is qualitative with interview as a technic to collect data from primer informan dan second informan. Result of this study is through instagram information about Lapo Mandailing Coffee can reach people that used Instagram in social media, so that thing can make sales Lapo Mandailing Coffee in promoting its product.